Simulation of hydrodynamic regime and longshore sediment transport in Cua Tung, Quang Tri - Trang, Nguyen Thi (Vietnam Journal of Marine Science and Technology, 2017)
This article presents simulation results, calculation of characteristics of wave-currents and sediment transport in Cua Tung, Quang Tri with different scenarios. Title of the topic “Evaluation of longshore and transversal transportation rates by the total impact of current - wave interaction using numerical model”. The results have been described in detail the hydrodynamic picture, the trend of erosion as well as the reasons for the imbalance in sediment balance in Cua Tung beach